Trade and migration linkages: The case of NAFTA - Philip L. Martin (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper reviews recent Mexico-US migration patterns and US reactions to Mexican immigration, explores why there may be a migration hump with two very different economies integrate, and discusses the policy options to deal with the extra migration associated with economic integration in North America. The major conclusion for policy makers is that a migration hump should be anticipated and dealt with; the major implication for economists is that the process of adjustment to new comparative statics equilibria can be important enough to affect economic integration itself. Migration represents one of the many asymmetries in Mexico-US relations- the United States accepts immigrants from many nations, but virtually all Mexican emigrants head for the United States. For most of the 20th Century, the US encouraged or tolerated a "go north for opportunity" mentality, especially in rural Mexico, so that, when Mexico experienced devaluations and economic shocks in the 1980s, many Mexicans "naturally" looked to the US as a safety valve. The economic integration symbolized by NAFTA was supposed to turn the "people relationship" between the US and Mexico into a "trade and investment relationship." US Presidents Bush and Clinton, and Mexican President Salinas, argued that economic integration was the best way to reduce emigration pressures in Mexico. In the words of Mexican President Salinas, "more jobs will mean higher wages in Mexico, and this in turn will mean fewer migrants to the United States and Canada. We want to export goods, not people." (quoted in Bush letter to Congress, May 1, 1991,17). The U.S. Commission for the Study of International Migration and Cooperative Economic Development, however, as well as most migration specialists, predicted that economic integration between the very different Mexican and the US economies would produce a migration hump-temporarily more migration, and then less, because "the economic development process itself tends in the short to medium term to stimulate migration." (Final Report, 1990, xvi). Economic integration and other policies that accelerate economic growth thus create "a very real short-term versus long-term dilemma" for the United States when dealing with unauthorized immigration, since the "the development Solution to unauthorized migration is measured in decades-even generations" (1990, xxxvi). NAFTA went into effect on January 1, 1994, a year that proved to be eventful in Mexico, with a Zapatista uprising, several political assassinations, and a peso devaluation. Legal immigration to the US, and apprehensions of unauthorized Mexicans, fell 10 to 20 percent in 1994, not as much as many expected. Some US politicians and immigration control advocates were able to use footage of "kamikaze" sprints by groups of unauthorized Mexicans through the US port of entry, as well as the lingering effects of recession, to re-elect California Governor Wilson and to approve Proposition 187, a State initiative that, if implemented, would make it more difficult for unauthorized aliens to obtain public services. The number of Mexican-born US residents appears to have increased sharply in the 1990s, supporting the proposition that migration hump is a feature of economic integration. There were 4.3 million legal and illegal Mexican-born residents enumerated in the 1990 Census, 6.3 million in the March 1994 CPS, and 6.7 million in the March 1995 CPS. Over 70 percent of the 1.1 million immigrants waiting to bring their spouses and children to the US are Mexicans and, by some estimates, most of them are already living in the US. Even more Mexicans are expected in the next five years. The number of people living in rural Mexico is likely to be halved from the current 24 to 27 million over the next 10 to 20 years, which means that 3 to 4 million rural households-which average 5 to 6 persons each- that now depend on farming must find nonfarm jobs within commuting distance of their current residences, migrate to Mexican cities for nonfarm jobs, or migrate to the US. Most migration specialists predict that, if Mexico grows at an average rate that is 2 to 3 percent faster than the US growth rate- something that Mexico has been unable to do in the 1990s- the economic gaps that motivate most legal and illegal Mexico to US migration will narrow, and Mexico-US migration will fall to "manageable" levels at about the time that new US immigration control efforts are put fully in place, or in 10 to 20 years. In other words, Mexico-US migration in the mid-1990s is believed to be near the peak of the "migration hump;" migration is expected to diminish after 2005.
Keywords: 330; Internationale Wanderung; Freihandelszone; Wirtschaftliche Anpassung; USA; Mexiko; NAFTA-Staaten